PENERAPAN MODEL PEMBELAJARAN PROBLEM SOLVING UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA MATERI SPLDV - Elfiyanti Ede; Natalia Peni; Hilaria Melania Mbagho (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2022)
This study aimed to determine the increase in student activity and learning outcomes in learning mathematics on the material of a two-variable system of linear equations. The background things are the low learning outcomes of students' mathematics. This is due to the use of an inappropriate teaching method approach. To overcome this, improvements can be made by applying a problem-solving learning model. This type of research is classroom action research (CAR). The subjects of this study were students of class X SMA Negeri 2 Jerebuu, totalling 14 people, consisting of 5 female students and 9 male students. Factors studied in the form of increased activity and student learning outcomes. Data collection methods used in this study were observation and test techniques. Data analysis used descriptive qualitative analysis with percentage technique. The results showed that the application of the problem-solving learning model could improve student activity and learning outcomes. Student learning activities in the first cycle obtained a total score of 29 with a percentage of 58% and were categorized quite well. Then it increased in the second cycle with the total score obtained being 43 and the percentage is 86% and categorized as very good. Student learning outcomes in the first cycle obtained an average of 70 with 50% of students achieving the Minimum Completeness Criteria (KKM). Then it increased in the second cycle with an average of 85.71 with 100% of students achieving KKM.